Dominant Factors Affecting the Level of Awareness of Sanitation Hygiene Implementation in Micro, Small and Medium Enterprises (MSMEs) - Suryani, Suryani; Has, Dwi Faqihatus Syarifah; Inayah, Zufra; Mindiharto, Sestiono (Ahmar Metastasis Health Journal, 2024)
The level of awareness of the application of sanitation hygiene in MSMEs in the Tuban Regency area is still low at around 80%. The purpose of this study was to analyze what factors influence the level of awareness of the application of sanitation hygiene. This research method uses quantitative research, analytical observational cross-sectional in nature. The population was all MSMEs in the Tuban Regency area that entered the Indonesian Electronic Business Licensing System on May 11, 2022, totaling 154 businesses. The sample size of 112 respondents was taken by simple random sampling. The independent variables included education level, knowledge, and attitude, while the level of awareness of sanitation hygiene implementation was the dependent variable. The instrument used a questionnaire sheet about the level of education, knowledge, and attitude, and a checklist sheet about the level of awareness of the application of sanitary hygiene. Analysis using Chi-Square test and Logistic Regression. The results showed that the level of education was almost half of elementary and junior high school graduates, and high school / vocational high school, 38.4% each, knowledge about the application of sanitation hygiene was mostly lacking, namely 67.0%, attitudes mostly had a negative response, namely 69.6%, the level of awareness of the application of sanitation hygiene was mostly low, namely 69.6%. Chi-Square test results, education level p value = 0.000, knowledge p value = 0.000, attitude p value = 0.000, and the results of the logistic regression test attitude has an OR value of 99.226 the highest. Thus, it can be concluded that there is a relationship between the level of education, knowledge, and attitude with the level of awareness in implementing sanitation and hygiene, where attitude is the most dominant factor. Therefore, it is necessary to increase knowledge about sanitation and hygiene for MSME actors, especially through food safety counseling for the home industry.